Meningkatkan Kecerdasan Kognitif Anak Usia Dini melalui Pendidikan Seni Melukis - Sunandar Azma'ul Hadi (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2021)
This type of research is a quasi-experimental which is included in quantitative research with posttest design only control desaign. The subjects in this study were 46 students consisting of experimental and control classes. Class A control (22 people) and class B experiment (24 people). The test instrument used in this study was a multiple choice question sheet. The results were analyzed using the t test. The results of the research analysis show that painting education can be used to improve early childhood cognitive abilities. The analysis conducted using SPSS showed that cognitive intelligence between groups A and B obtained a significant value of 0.762. Because the significant value is > 0.05, the hypothesis of this study is accepted.